Experimental and Numerical Investigation of Octagonal Partially Encased Composite Columns Subject to Axial and Torsion Moment Loading - Mehdi Ebadi Jamkhaneh; Mohammad Ali Kafi (Salehan Institute of Higher Education, 2017)
This paper includes experimental and numerical study of the octagonal partially encased composite (PEC) columns specimens under axial and torsion loading. The major difference between them was the concrete reinforcement details. The parameters investigated in the experimental and numerical study were the type of reinforcement details, the failure mode, width-to-thickness ratio of flange, transverse links spacing and diameter. The results were presented as load-deformation curves. Numerical model was validated using finite element method and the results indicated acceptable accuracy with tests results in the form of capacity and ductility. In the analytical phase, the experimental results in the compressive loading were compared with those obtained from CSA S16-14 and EN 1994-1-1 equations. Also, the new concrete confinement factor in proportion to the web width to thickness ratio was presented to octagonal PEC columns under pure compressive load. Furthermore, different types of retrofit of cross-shaped steel column including concrete encasement, use of stiffener plates and transverse links were investigated in this research. Results revealed that concrete confinement and use of transverse links had respectively the most and the least effect on increasing torsional capacity of the specimens.